Experimental Assessment of Gas Static Meters Under Different Operating Conditions. Issue 1 (April 2021) - Cascetta, Furio; Bondesan, Marcello; Musto, Marilena; Rotondo, Giuseppe
Abstract: This paper compares the metrological performance of a sample of commercial domestic/residential smart meters for natural gas (G4). In particular, the performance degradation of electronic static and dynamic gas meters has been evaluated. The sample was composed by ultrasonic gas meters, thermal mass meters and diaphragm gas meters. The tests, performed on the gas meters, reproduce the most severe operating conditions (i.e. filed test) such as the influence of the gas composition, the temperature difference between gas and meter, the gas humidity and the presence of dust in the gas. Furthermore, the meters have been undergo to some endurance tests such as start and stop and to the high flowrate runs.